1982
DOI: 10.1084/jem.156.4.1177
|View full text |Cite
|
Sign up to set email alerts
|

Anti-phosphorylcholine antibodies of the T15 idiotype are optimally protective against Streptococcus pneumoniae.

Abstract: In the mouse, most anti-PC antibody is found in one of the three murine anti-PC idiotype families: T15, M603, or M511. The antibodies within each of these idiotypic families have characteristic fine specificities for phosphorylcholine (PC)-analogues. In this paper we compare the ability of hybridoma IgM anti-PC antibodies of the three idiotype families to protect mice from fatal infection with S. pneumoniae. Antibody bearing the T15 idiotype was approximately 8 times as effective as antibody with the M603 idio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
188
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(189 citation statements)
references
References 26 publications
1
188
0
Order By: Relevance
“…A capsular type 3 pneumococcal strain (WU2, PspA ϩ ) (24,25) and its isogenic mutant (JY1119, PspA Ϫ ) (4,7,26) were used. Bacterial stocks were frozen at Ϫ80°C in Todd-Hewitt broth supplemented with 0.5% yeast extract containing 10% glycerol.…”
Section: Bacteria and Infectionsmentioning
confidence: 99%
“…A capsular type 3 pneumococcal strain (WU2, PspA ϩ ) (24,25) and its isogenic mutant (JY1119, PspA Ϫ ) (4,7,26) were used. Bacterial stocks were frozen at Ϫ80°C in Todd-Hewitt broth supplemented with 0.5% yeast extract containing 10% glycerol.…”
Section: Bacteria and Infectionsmentioning
confidence: 99%
“…Genetic analysis indicated that EO6, the prototypic IgM anti-OxLDL antibody, was a natural antibody secreted by innate B-1 cells in a T cell-independent (TI) manner and possessed the germline-encoded T15 clonotype (8). T15 antibodies have previously been shown to recognize the PC moiety (10), which is an immunodominant component of the cell wall of many microbes, such as Streptococcus pneumoniae (11). Our previous studies show that T15/EO6 also recognizes the PC moiety of oxidized phospholipids, as present on OxLDL and apoptotic cells, but does not recognize native PC-containing unoxidized phospholipids, as found on native LDL or viable cells (8).…”
Section: Introductionmentioning
confidence: 99%
“…The institutional animal care and use committee approved all animal studies. All experiments were performed with 8-to 12-week-old CBA/N mice (Jackson Laboratory) (Briles et al, 1982). Pneumococci were grown at 37 uC in 5% CO 2 in THY medium.…”
mentioning
confidence: 99%